(3GdEaUGM Yf EYQGH CHjGJ eTcdI GdEjVGMs - (3CHhfUQ GdMSf Hf CSO Hf GdMSf GdaGQbj,J (B487 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEffj CWGd Gddg HbGAc deG hbaJ Ydi TQja efRdJc hefja QJHJc s
(3BNQgG (B:s
(3LQ HGdYWa Ydi TQ, cGf GdJbOjQ hHDS fdbi dOjce GdCPi BNQ GdLRA GdChd ef GdEaUGM s
(3fSNI KGfjI JJab aj ChdgG eY Chd GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B206s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B43 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B27 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdfMhs